Random access improvement for M2M communication in LTE-A using femtocell - Eric Sackey; Rajeev Paulus (International Journal of Electrical and Computer Engineering (IJECE), 2019)
When an area is highly populated with Machine-to-Machine devices and all these devices attempt to access the Random Access Network Simultaneously, congestion is created on the network which degrades the performance of the network to other users. In this paper, the researchers are seeking to improve network accessibility by deploying more Femtocell into the network. They engaged the use of Extended Access Barring to restrict the M2M devices from accessing the network via macrocell eNB when a minimum load threshold is attained, thereby preventing the macrocell eNB from being congested. Deploying these Femtocells underneath the macrocell eNB comes with the issue of Inter-Cell Interference which nullifies any gains made by this deployment. The researchers employed Fractional Frequency Reuse and Complete Frequency Reuse schemes to mitigate the negative effects of ICI to augment the throughput of the network, improve the system capacity and enhanced the user experience within the network.